Distal radial artery ligation for dialysis access-associated ischemic syndrome - ZHANG Li-hong; ZHAN Shen; YANG Tao; WANG Yu-zhu (Linchuang shenzangbing zazhi)
Objective To summarize the experience of treatment for dialysis access-associated ischemic steal syndrome by ligating distal radial artery of radial cephalic fistulas(RCFs).Methods We enrolled hemodialysis patients who used RCFs with complaint of ipsilateral limb ischemia admitted in our department Anatomical prerequisites(side-to-end anastomosis fistula and retrograde flow in the distal radial artery) were checked by ultrasound,the patency of central artery by angiography,and the function of ulnar artery by Allen test Division and ligation of the juxta-anastomosis distal radial artery were performed under regional anesthesia.Clinical presentation,blood flow during hemodialysis,urea clearance index,urea reduction rate,and fistula patency were observed before and after operation.Results This study included 16 patients(8 males and 8 females,accounting for roughly 1.45%of hospitalizations of patients associated with fistula complications at the corresponding time) who underwent DRAL of RCFs with ischemia,of whom the mean age was(66.2 ± 11.2) years,fistula age was(57.75 ± 88.41) months,and the ischemia was detected(39.62 ± 58.31) months after the construction of fistula.According to clinical presentation,71.40%patients were grade Ⅲ,28.60%were grade Ⅱ,and no patients belonged to grade Ⅳ.The technique success rate was 100%and clinical success rate was 93.7%.Blood flow during hemodialysis before and 7 days,6 months and 12 months after operation was(258.63 + 25.44),(246.61 ± 24.24),(260.42 ± 20.83) and(254.87 ± 22.44) ml/min(P>0.05),and Kt/V was(1.65 ± 0.210),(1.59 +0.24),(1.62±0.28) and(1.58 ±0.39)(P>0.05),respectively.The mean follow-up duration was(19.30 ± 13.15) months and the patency rate was 100%.Conclusions DRAL is a simple,safe,and effective technique for dialysis access-associated ischemic syndrome in RCFs.